ON THE IMPACT OF GOVERNMENT REGULATION ON THE DEVELOPMENT OF ENTREPRENEURIAL ACTIVITIES OF BUSINESS ENTITIES IN THE FIELD OF HEALTH PROTECTION AND VALUE-ADDED (PROFIT) EXTRACTION IN THE MEDICAL SERVICES MARKET - Лебедев, Александр Александрович; Эрдыниева, Людмила Салчаковна (Medicine in Kuzbass, 2025)
The article considers issues related to the formation and extraction of profit from the implementation of medical activities by economic entities in the healthcare sector. The issues of administrative influence of the state on the activities of medical organizations of various forms of ownership that carry out entrepreneurial activities in the medical services market are analyzed. Legislative, organizational, economic aspects of medical activities are considered for the purpose of forming and extracting profit in accordance with legislatively established sources of financing in the healthcare sector. The methodological basis of the study is general scientific and specific scientific methods, such as formal-legal, analytical, system analysis, statistical, economic. The scientific novelty of the work lies in the conclusions proposed by the author based on the results of the study. Based on the analysis of the norms of the current legislation, it is concluded that at the current time, profit from medical activities can be extracted by economic entities in the healthcare sector when providing consumers with paid medical services. The author expresses the point of view that the principles of financial support in the sphere of public health protection, currently established within the framework of compulsory medical insurance and budget financing, do not provide for the possibility of making a profit from medical activities, which is the result of the social policy pursued by the state in the sphere of public health protection.
Keywords: entrepreneurial activity; medical activity; private medicine; private medical organization; profit; paid services; compulsory medical insurance; voluntary medical insurance; budget financing; profitability; purchasing power parity; legislation; welfare st